2016
DOI: 10.1186/s12936-015-1064-x
|View full text |Cite
|
Sign up to set email alerts
|

Status of the use and compliance with malaria rapid diagnostic tests in formal private health facilities in Nigeria

Abstract: Background Nigeria has the largest number of malaria-related deaths, accounting for a third of global malaria deaths. It is important that the country attains universal coverage of key malaria interventions, one of which is the policy of universal testing before treatment, which the country has recently adopted. However, there is a dearth of data on its implementation in formal private health facilities, where close to a third of the population seek health care. This study identified the level of use of malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 41 publications
2
37
0
1
Order By: Relevance
“…The study showed that healthcare workers have good knowledge of mRDT similar to a study conducted in Southeast Nigeria where 61.1% of respondents knew about mRDT. 24 The proportion of healthcare workers who knew the meaning of mRDT was found to be higher than that in a study carried out in the six geo-political zones of Nigeria where 70% reported knowing the meaning of mRDT 21 . This is probably because of investment by government and non-governmental organizations in awareness creation on parasitological testing through training on mRDT 21 in Zamfara state.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The study showed that healthcare workers have good knowledge of mRDT similar to a study conducted in Southeast Nigeria where 61.1% of respondents knew about mRDT. 24 The proportion of healthcare workers who knew the meaning of mRDT was found to be higher than that in a study carried out in the six geo-political zones of Nigeria where 70% reported knowing the meaning of mRDT 21 . This is probably because of investment by government and non-governmental organizations in awareness creation on parasitological testing through training on mRDT 21 in Zamfara state.…”
Section: Discussionmentioning
confidence: 55%
“…Factors such as heavy workload, lack of trust, cost, training on the use of RDTs have been considered to influence RDT use 1621 . A study reported a high proportion (61.5%) of healthcare workers perceived mRDTs as unreliable, one-third (30.8%) of healthcare workers had supply issues with mRDT, 15.4% of them reported a preference for other methods of malaria diagnosis and one-fifth (26%) of healthcare workers were ignorant about mRDT.…”
Section: Introductionmentioning
confidence: 99%
“…We purposively selected public healthcare providers (4), TBAs (4) and faith-based birth attendants (4) based on popularity and accessibility within selected communities, to explore access and awareness surrounding IPTp in a pluralistic health sector. We further purposively contacted community leaders (7) and caregivers, mainly, family members (20), through participating pregnant women (30), to enable us to explore the in uence of community and family networks on IPTp access and uptake. SSIs were conducted in the local language (Yoruba) and/or English with each interview ranging from 30 to 65 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is scant evidence on how interpersonal, societal and provider related factors contribute to the poor uptake of ITNs and IPTp, particularly in rural and lower socioeconomic communities where social and communal norms are most in uential. This is relevant as Nigeria operates a pluralistic health sector with about 60% of Nigerians seeking private health care (7,8). Traditional Birth Attendants (TBAs) and faith-based birth attendants, as key parts of the private health sector, provide a signi cant amount of ANC services (9,10), especially in rural and lower socio-economic communities.…”
Section: Introductionmentioning
confidence: 99%
“…However, its underperformance can be catastrophic resulting in biased investments, planning and poor health outcomes. Studies have shown the RHIS in Nigeria to be inadequate to support mental health, maternal and child health, malaria, and disease surveillance decisions (Makinde, ; Mokuolu et al., ; Nnebue, Onwasigwe, Ibeh, & Adogu, ; Upadhaya et al., ; Wollum, Burstein, Fullman, Dwyer‐Lindgren, & Gakidou, ). Efforts aimed at addressing the RHIS are exploring the deployment of mobile enabled applications to improve the timeliness and completeness of reports (Asangansi & Braa, ; Asangansi et al., ).…”
Section: Introductionmentioning
confidence: 99%